A Longitudinal Analysis of the Indonesian Production Sharing Contracts (Psc): The Question of Economic Accountability - Sihotang, Parulian (Journal the Winners: Economics, Business, Management, and Information System Journal, 2003)
The article objective is to describe a longitudinal analysis of the Indonesian Production Sharing Contracts (PSC). Article presents the history of petroleum contractual agreements in Indonesia, selected indicators to evaluate PSCs performance, the statistical techniques used to analyze the data, statistical results, operational indicators, discussion of results and linkage to concept of accountability. The conclusion is the longitudinal study on the PSCs performance over the last 30 years have indicated that the current structure of the agreements seemed to have failed in supporting the dynamic contractual accountability between the host country and the FOCs. The PSCs lacked the capability to promote both host country and FOCs’ interests in a fair and reasonable way.